Pneumatic pressure control system with microcontroller on bullet tower - Umar, Ali; Rezwandi, Fiqri Aqilah; Rohman, Hamzah Nur; Prasasti, Anggunmeka Luhur; Tresna, Wildan Panji (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2025)
A bullet launcher is a defense tool intended to shoot targets, powered by gunpowder that can endanger its users. The use of gunpowder is dangerous because the resulting explosive power can harm the user. An alternative solution that can be done for this problem is to design a bullet launcher system that does not endanger its users. the system that has been implemented is a pneumatically powered bullet launcher. The pneumatic system is controlled using a microcontroller to control the input of sensors, solenoids, actuators and air pressure in the system. The pressure sensor used is a WPT-83G-EGG4 transmitter with a maximum pressure of 12 bar or 174 psi. The test results obtained with the average pressure measurement error is ±1% tolerance at pressures below 33 psi. The average response time of the sensor detecting pressure is 0.2 seconds.